2002
DOI: 10.1677/erc.0.0090033
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against the HER-2/neu oncogenic protein.

Abstract: The HER-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…A novel approach toward the treatment of HER-2-positive breast cancer has been the use of vaccines and adoptive immunotherapy targeting HER-2 ECD [367][368][369][370][371]. HER-2-specific vaccines have been tested in human clinical trials that have shown that significant levels of durable T-cell HER-2 immunity can be generated with active immunization.…”
Section: Her-2 Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel approach toward the treatment of HER-2-positive breast cancer has been the use of vaccines and adoptive immunotherapy targeting HER-2 ECD [367][368][369][370][371]. HER-2-specific vaccines have been tested in human clinical trials that have shown that significant levels of durable T-cell HER-2 immunity can be generated with active immunization.…”
Section: Her-2 Vaccinesmentioning
confidence: 99%
“…HER-2-specific vaccines have been tested in human clinical trials that have shown that significant levels of durable T-cell HER-2 immunity can be generated with active immunization. No significant autoimmunity directed against normal tissues has been encountered [368]. Moreover, active anti-HER-2 immunization could facilitate the ex vivo expansion of HER-2-specific T cells for use in adoptive immunotherapy for the treatment of established metastatic disease [367].…”
Section: Her-2 Vaccinesmentioning
confidence: 99%
“…3 Several strategies against HER2/neu have been proposed and DNA vaccination represents an optimal methodology for activating the immune system against HER2/neu. 4 Various studies, some of which were carried out by our group, confirmed the possibility of inducing HER2/neu-specific immunity in HER2/neu transgenic mice by DNA vaccination with plasmids encoding fulllength or truncated HER2/neu. [5][6][7][8][9] In the investigated models, DNA vaccination inhibited tumour development according to vaccine properties; the use of molecules playing critical regulatory and signalling roles in immunity, such as immunomodulatory cytokines and costimulatory molecules, increased the effectiveness of DNA vaccines in terms of tumour prevention.…”
Section: Introductionmentioning
confidence: 97%
“…Examples of CTAs currently being used for immunotherapy include NY-ESO-1 and MAGE-A3 peptides in melanoma (Coulie et al, 2001;Jäger et al, 2001). However, it should be noted that other categories of SEREX antigens, such as the overexpressed HER-2/neu protein, are being targeted with some success in the treatment of breast carcinomas (Bernhard et al, 2002). SEREX antigens can also be used as adjuvants to boost the immune response to other tumour antigens (Nishikawa et al, 2001).…”
mentioning
confidence: 99%